Health Promotion Interventions in Sports Clubs: Can We Talk About a Setting-Based Approach? A Systematic Mapping Review. (August 2019) - Geidne, Susanna; Kokko, Sami; Lane, Aoife; Ooms, Linda; Vuillemin, Anne; Seghers, Jan; Koski, Pasi; Kudlacek, Michal; Johnson, Stacey; Van Hoye, Aurélie
Many researchers and authorities have recognized the important role that sports clubs can play in public health. In spite of attempts to create a theoretical framework in the early 2000s, a thorough understanding of sports clubs as a setting for health promotion (HP) is lacking. Despite calls for more effective, sustainable, and theoretically grounded interventions, previous literature reviews have identified no controlled studies assessing HP interventions in sports clubs. This systematic mapping review details how the settings-based approach is applied through HP interventions in sports clubs and highlights facilitators and barriers for sports clubs to become health-promoting settings. In addition, the mapped facilitators and barriers have been used to reformulate previous guidelines of HP in sports clubs. Seven databases were searched for empirical research published between 1986 and 2017. Fifty-eight studies were included, principally coming from Australia and Europe, describing 33 unique interventions, which targeted mostly male participants in team sports. The settings-based approach was not yet applied in sports clubs, as more than half of the interventions implemented in sports club targeted only one level of the socio-ecological model, as well as focused only on study participants rather than the club overall. Based on empirical data, the analysis of facilitators and barriers helped develop revised guidelines for sports clubs to implement settings-based HP. This will be particularly useful when implementing HP initiatives to aid in the development of sports clubs working with a whole setting approach.